Furanodiene: A Novel, Potent, and Multitarget Cancer-fighting Terpenoid - Batool, Rabia; Rasul, Azhar; Hussain, Ghulam; Shah, Muhammad A.; Nageen, Bushra; Sarfraz, Iqra; Zahoor, Muhammad Kashif; Riaz, Ammara; Ajaz, Aiza; Adem, Şevki (Current Pharmaceutical Design, 2021)
Natural products have served as a limitless reservoir of bioactive scaffolds for drug discovery against several disorders. Furanodiene is a bioactive natural product isolated from several plants of genus Curcuma. Its therapeutic potential against cancer, inflammation, and angiogenesis has been well-documented. The current review is an update about the natural sources and anti-cancer action mechanism of furanodiene. Furanodiene exerts its anti-cancer effects via induction of apoptosis in several cancer types by modulating MAPKs/ERK, NF-ΚB, and Akt pathways. Furanodiene has been systematically studied for its anti-cancer potential. However, pharmacokinetics, pharmacodynamics, pre-clinical and clinical studies still needed to be conducted to completely validate the potential of furanodiene for the treatment of cancer.
Keywords: Curcuma